AB0006 ASSOCIATION OF HLA-DPB1*16:01 ALLELE WITH PR3-ANCA POSITIVE GRANULOMATOSIS WITH POLYANGIITIS IN TURKISH PATIENTS. (June 2019) - Ince, Burak; Kamali, Sevil; Ogret, Yeliz Duvarci; Oguz, Fatma Savran; Artim-Esen, Bahar; Inanc, Murat; Lale Ocal, Mahdume; Gül, Ahmet
Abstract : Background: ANCA associated vasculitides (AAV) comprise an important subset of small vessel vasculitides with a multifactorial pathogenesis, which is considered to be associated with the interaction of genetic and environmental factors. Certain HLA Class 2 alleles have been reported among the genetic risk factors for AAV from different geographic regions such as Europe and Asia (1, 2). Objectives: In this study, we aimed to analyse the distribution of HLA Class 2 genotypes among a series of Turkish AAV patients in comparison with the healthy Turkish subjects and the previously reported data of AAV cohorts from other countries. Methods: Ninety-eight patients (aged between 18–75 years) diagnosed with AAV according to 2012 Chapel Hill Consensus Criteria were enrolled into the study. Records of age-and birthplace-matched 196 healthy kidney donors were used as the control group. Patients were classified according to the clinical subgroups (GPA, e-GPA, MPA) and ANCA serotypes (MPO-AAV, PR3-AAV). HLA Class II genotyping were carried out by using NGS-Omixon Holotype HLA Kit at the EFI accredited HLA Typing Lab of Department of Medical Biology. Allele distributions were compared by Chi-square test, and P value lower than 0.05 was accepted as significant. Results: AAV patients were classified as PR3-AAV (54%) and MPO-AAV (31.6%) according to autoantibodies and GPA (71.4%), MPA(20.4%), e-GPA(8.2%) according to clinical subgroups. HLA-DPB1*04:01 (8.5% vs. 35.9% p<0.01, OR= 0.16 %95 CI 0.08–0.34) and HLA-DPB1*02:01 (%7.5 vs. %22.4 p<0.05, OR=0.28 %95 CI 0.13–0.6) alleles were significantly lower in the PR3-AAV group. HLA-DPB1*16:01 allele was significantly higher in the PR3-AAV group (%8.5 vs. %0.26 p<0.01, OR=36.2 %95 CI 4.5–289.7). In clinical subgroups, HLA-DPB1*04:01 (%7.9 vs. %35.9 p<0.01, OR=0.15 %95 CI 0.08–0.29) and HLA-DPB1*02:01 (%7.9 vs. %22.4 p<0.01 OR= 0.29 %95 CI 0.15–0.57) alleles were significantly lower in the GPA-AAV group. HLA-DPB1*16:01 allele was significantly higher in the GPA-AAV group (%7.14 vs. %0.26 p<0.01, OR=30, %95 CI: 3.8–237). No significant difference was detected between the MPO-AAV and control groups. Conclusion: HLA analysis of this small series of Turkish AAV patients revealed a negative correlation between PR3-ANCA positivity and HLA-DPB1*04:01 and HLA-DPB1*02:01 alleles in opposition to the results reported from different European AAV cohorts (1, 3). On the other hand, a significant increase in both GPA and PR3-AAV subgroups for a previously unpublished HLA-DPB1*16:01 allele may suggest that HLA association may show ethnic or regional differences, and further analyses in larger series of AAV patients may reveal the molecular basis of this observation. References: [1] Lyons PA, Rayner TF, Trivedi S, et al. Genetically distinct subsets within ANCA-associated vasculitis. N Engl J Med 2012; 367:214-223. [2] Tsuchiya N. Genetics of ANCA-associated vasculitis in Japan: a role for HLA-DRB1*09:01 haplotype. Clin Exp Nephrol 2013; 17:628–630. [3] Xie G, Roshandel D, Sherva R, et al. Association of granulomatosis with polyangiitis (Wegener's) with HLA-DPB1*04 and SEMA6A gene variants: evidence from genome-wide analysis. Arthritis Rheum. 2013;65(9):2457-68. Disclosure of Interests: None declared